PERKEMBANGAN ISLAM ARAB SAUDI - Wahyuddin, Imam (P3M STAIN Sorong, 2018)
The kingdom of al-SaÅ«diyah actually existed since 1446. However, as a strong dynasty and established the Saudi Arabia state is since the era of Abd. Aziz ibn Abd. Rahman al-Saud (Ibn Saud) with the spirit of Wahhabism and British aid. Officially in 1932 the Kingdom of Saudi Arabia became an Islamic state with a monarchic system under King Ibn Saud. This paper will discuss the history of Islamic development in Saudi Arabia which is now as an Islamic State. Saudi Arabia is now dominated by the kingdom of al-SaÅ«diyah which is influenced by Wahabiyah religious beliefs. From the beginning of the nineteenth century the Wahabiyah movement received support from Muhammad Ibn Saud. They began expansion which culminated in the conquest of most of the Arabian peninsula and made social, religious and political set agendas in Saudi Arabia. Wahabiyah continues to expand and exist in Saudi Arabia, especially in the mid-19th to the 20th century, and its development pattern is based on top down. Thus, the development of Islam in Saudi Arabia can not be separated from Wahabiyah influence. In the midst of social change, Saudi authorities continue to maintain Wahabiyah as a royal religious ideology. In fact, Wahabiyah ulama also play a role in giving religious approval to the policies of the royal government. However, other factors that also make Islam flourish in Saudi Arabia are the historic impact as the main influence of Muslims since the Prophet era and Saudi Arabias strategic position for various informationÂ reforms in the Islamic world as it controls Mecca and Medina as the sacred city (Haramain). On the other hand, the development of Islam in Saudi Arabia can also be seen in terms of Islamic politics played by the royal government and its foreign political economy which is deemed to be close to the Brtish, US or the West in the Middle East, preferably in the Israel and Palestinian conflict.